The trickster in Egypt's January 25th revolution - Armbrust, W (Cambridge University Press, 2013)
The term “counter-revolution” evokes a straightforward contestation of political claims in a revolutionary situation. But contestation is not a zero-sum game: this side wins; the other side loses, and power remains the same. A revolutionary situation is unpredictable. New formulations of political claims may emerge in a protracted moment of “liminal crisis”—a kind of political ritual with no master of ceremonies capable of ending it. Indeed, the meaning of the political prize itself might be open to reinterpretation. My paper examines counter-revolution through the lens of Taufiq ‘Ukasha, an Egyptian talk show host and former member of the deposed National Democratic Party. Since the Revolution ‘Ukasha has become increasingly prominent as an unacknowledged spokesman for Egypt's Military Council, which assumed executive powers in the wake of the Mubarak regime's collapse. I argue that ‘Ukasha should not be understood simply as a filul—a remnant of the old regime. He is rather a “trickster,” a creature at home in the betwixt-and-between of open-ended liminality, and as such not an instrument of a socially grounded political power. In an environment in which the usual points of social and political orientation are called into question, the significance of a trickster is that he or she can become an object of emulation, an instrument of “schismogenesis”—the creation of a new social formation. A trickster, as a creature of pure liminality, is particularly prone to generating perverted forms of social knowledge. In ‘Ukasha's case, this new social formation is an unprecedented formulation of Egyptian militarism.